Penerapan Bi’Ah Arabiyah Untuk Meningkatkan Maharah Kalam Santriwati Pondok Pesantren Riyadlul Qur’An - Arifah Liqo’ Robbani; Mu’at Mu’at (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Arabic Language EnvironmentArabic language education in Indonesia plays a very important role, especially In Islamic educational institutions such as pesantren. Riyadlul Qur'an Islamic Boarding School in Mojokerto, which focuses primarily on teaching the Qur'an through memorization, has implemented a policy of using Arabic in the daily lives of its students. The uniqueness of this boarding school lies in its ability to integrate Quranic education with an Arabic-language environment. The study employs a qualitative methodology with a case study approach. Data were gathered through multiple methods such as direct observation, detailed interviews, and document analysis involving the caregivers, teachers, mudabbiroh, and female students as the main sources of information. Meanwhile, The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The research findings presented by the researcher are as follows: (1) The Arabic-language environment at the Riyadhul Qur’an Islamic Boarding School in Mojokerto has proven to be highly significant in improving the speaking skills of female students. This environment is created through mandatory Arabic language policies, daily vocabulary practice (mufrodat), a language monitoring system (jasus), and the active role of teachers and mudabbiroh as mentors who encourage the use of Arabic in daily life. (2) Supporting factors identified in this study include consistent policies from the boarding school, teacher involvement, and adequate facilities. On the other hand, inhibiting factors include the students' lack of Arabic language foundation, the use of local dialects in daily communication, and fear of speaking due to concerns about making mistakes. This study concludes that a well-structured Arabic-language environment can enhance female students' speaking ability, as evidenced by their continued use of Arabic in communication even after graduating from the boarding school.